Paeoniflorin Ameliorates Macrophage Infiltration and Activation by Inhibiting the TLR4 Signaling Pathway in Diabetic Nephropathy - Shao, Yun-xia; Gong, Qian; Qi, Xiang-Ming; Wang, Kun; Wu, Yong-gui (Frontiers in Pharmacology, 2019)
Paeoniflorin (PF) is the primary component of total glucosides of paeony (TGP). It exerts multiple effects, including immunoregulatory and anti-inflammatory effects. Our previous study has found that PF has a remarkable renal-protective effect in diabetic mice, but exact mechanism has not been clarified. This study mainly explores whether PF affects macrophage infiltration and activation in diabetic kidney through TLR4 pathway. Thus, this study was conducted to investigate the effect of PF on a streptozotocin (STZ)-induced experimental DN model. The results suggested that the onset and clinical symptoms of DN in mice were remarkably ameliorated after the administration of PF. Moreover, the number of infiltrating macrophages in the mouse kidneys was also markedly decreased. Instead of inhibiting the activation of macrophages directly, PF could influence macrophages by suppressing iNOS expression as well as the production of TNF-α, IL-1β, and MCP-1 both in vivo and in vitro. These effects might be attributable to the inhibition of the TLR4 signaling pathway. The percentage of M1-phenotype cells as well as the mRNA levels of iNOS, TNF-α, IL-1β, and MCP-1 were downregulated when PF-treated polarized macrophages were cultured under conditions of high glucose (HG) levels. In addition, the expression of TLR4, along with that of downstream signaling molecule proteins, was also reduced. Our study has provided new insights into the potential of PF as a promising therapeutic agent for treating DN and has illustrated the underlying mechanism of PF from a new perspective.